Advanced practice nursing leadership : a global perspective - Accad, Aila; Adams, Sue; Al-Darazi, Fariba; Al-Maqbali, Majid; Anathan, Julie; Hassmiller, Susan B. 1954-; Pulcini, Joyce (Switzerland : Springer, 2020)
This book is distinctive in its focus on Advanced Practice Nursing leadership globally. It has a unique structure, first highlighting global APN leadership and then including case studies on leadership from various regions around the world. This beneficial and practical book has a specific emphasis on academic, clinical and policy leadership and is relevant for all readers. Finally, a section on leadership development focuses on coaching and mentoring, business acumen, collaboration and patient advocacy provides an important contribution.
La función de los autores fue determinada por el catalogador
Tambien disponible en formato EPUB
Keywords: PRACTICANTES DE ENFERMERÍA; LIDERAZGO; ENFERMERIA Y ENFERMERAS -- ESTUDIO Y ENSEÑANZA; ENFERMERÍA DE PRÁCTICA AVANZADA